New allele of HvBRI1 gene encoding brassinosteroid receptor in barley - Gruszka, Damian (Springer-Verlag, 2011)
The aim of these studies was to characterize nucleotide substitutions leading to the phenotype of brassinosteroid-insensitive, semi-dwarf barley mutant 093AR. Two substitutions in the sequence of barley HvBRI1 gene, encoding leucine-rich repeats receptor kinase (LRR-RK), which participates in brassinosteroid (BR) signalling, were identified in this chemically-induced barley mutant of the cv. Aramir. The LRR-RK is a transmembrane protein phosphorylating downstream components. The identified substitutions CC>AA at positions 1760 and 1761 in the HvBRI1 gene of this mutant led to a missense mutation, causing the Thr-573 to Lys-573 replacement in the protein sequence. The threonine residue is situated in the distal part of a 70-amino acids island responsible for binding of BR molecules. As this residue is conserved among BRI1 protein homologs in Arabidopsis thaliana, Lycopersicon esculentum, Oryza sativa and Hordeum vulgare, it was postulated that this residue is crucial for the protein function. The genetic analyses indicated that the mutant 093AR was allelic to the spontaneous, semi-dwarf mutant uzu which carries A>G substitution at position 2612 of the HvBRI1 gene (GenBank acc. no. AB088206). A comparison of the genomic sequence of HvBRI1 in the mutants uzu, 093AR and in the cv. ‘Aramir’ confirmed the presence of the single-nucleotide A>G substitution at position 2612 in the sequence encoding kinase domain of HvBRI1 polypeptide in uzu, but not in 093AR mutant, indicating that a new allele of the HvBRI1 gene was identified.